Nuclear mechanics & genome regulation - Shivashankar, G. V.; ScienceDirect eBooks (Amsterdam, Netherlands ; Boston, Mass. : Elsevier/ Academic Press, 2010)
In recent years new discoveries have made this an exciting and important field of research. This comprehensive volume presents€comprehensive chapters and detailed background information for researchers working with in the field of Nuclear Mechanics and Genome Regulation. * Both classic and state-of-the-art methods readily adaptable and designed to last the test of time * Relevant to clinicians and scientists working in a wide range of fields.
Cover; Methods in Cell Biology; Copyright; Contents; Contributors; Preface; Section A. Cell Nucleus: Organization & MechanoBiology; Section B. Impact of Nuclear Mechanics on Function; Subject Index; Volumes in Series.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Genomics; Genetic regulation; Nuclear physics; SCIENCE -- Life Sciences -- Genetics & Genomics; Genetic regulation; Genomics; Nuclear physics; Cell Nucleus -- metabolism; Gene Expression Regulation; Genomics; Electronic books